2021
DOI: 10.3390/ijerph182212166
|View full text |Cite
|
Sign up to set email alerts
|

Firm-Value Effects of Carbon Emissions and Carbon Disclosures—Evidence from Korea

Abstract: We examine the association between carbon emissions, carbon disclosures, and firm value for Korean firms, with a particular interest in chaebols, a special type of Korean conglomerate. Using hand-collected carbon emissions and firm-specific data for 841 Korean firms, including 514 chaebols and 335 non-chaebols, we find a significantly positive relationship between carbon emissions and firm value among chaebol affiliates. This result contrasts with previous findings conducted in advanced markets, where investor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…Specifically, voluntary disclosure is called so because managers voluntarily choose whether to disclose information on corporate carbon emissions, and there is no special penalty for not disclosing due to the nature of voluntary disclosure. Recently, research on the disclosure of carbon emission information by companies has been actively conducted, but only a small number of studies have been conducted in South Korea for the reason of securing data [ 14 , 15 , 16 , 17 , 18 ]. Briefly introducing domestic studies conducted with carbon emission information data surveyed by CDP institutions such as this paper, there are studies showing that the higher the carbon emission information, the higher the corporate value, and the higher the share of foreign investors, the higher the tendency to disclose carbon emission information.…”
Section: Backgrounds and Hypothesesmentioning
confidence: 99%
“…Specifically, voluntary disclosure is called so because managers voluntarily choose whether to disclose information on corporate carbon emissions, and there is no special penalty for not disclosing due to the nature of voluntary disclosure. Recently, research on the disclosure of carbon emission information by companies has been actively conducted, but only a small number of studies have been conducted in South Korea for the reason of securing data [ 14 , 15 , 16 , 17 , 18 ]. Briefly introducing domestic studies conducted with carbon emission information data surveyed by CDP institutions such as this paper, there are studies showing that the higher the carbon emission information, the higher the corporate value, and the higher the share of foreign investors, the higher the tendency to disclose carbon emission information.…”
Section: Backgrounds and Hypothesesmentioning
confidence: 99%
“…9 Firms adopting ESG management practices may voluntarily disclose carbon emission information because such disclosure is considered the first step in addressing climate change, a key aspect of ESG practices. 5 Empirical studies on carbon emissions often utilize data from the CDP. The CDP is a nonprofit institution that collects global data on firms' carbon disclosure.…”
Section: Firm's Tendency To Carbon Disclosurementioning
confidence: 99%
“…Several studies in the Korean market use CDP reports to determine whether firms disclose their carbon emissions. For example, using CDP data, Lee and Cho (2021) in Korea found that Korean firms with higher environmental performance are likely to voluntarily disclose their carbon emissions. 5 They also emphasize the importance of firm heterogeneity, such as corporate governance structure, in the decision-making process for voluntary disclosure.…”
Section: Korean Market and Firms' Carbon Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…Enterprises whose actual emissions exceed the quotas must purchase the quotas of the excess emissions to complete the appointment (Sadawi et al, 2021). Lee and Cho (2021) examined the economic consequences of carbon trading and suggested that the implementation of carbon trading can promote the increase of firm value. Yu (2018) concluded that the implementation of carbon emissions has a significant positive impact on corporate sustainable development, indicating that carbon reduction is beneficial to the ecological environment and corporate sustainability.…”
Section: Introductionmentioning
confidence: 99%